ARUS KAS DAN NILAI UANG (Sebuah Critical Review) - Sukirman, Sukirman (MIIPS, 2008)
We can consider value from two different perspectives. The first is the present value of expected cash flows, or what we will call financial value.The second Â is market value, which reflects what investors are willing to pay for the invesment as they understand it. If information is easily available to all investor and the markets are fairly efficient, we might expect market value to reflect the financial value quite efficient.However, these two values may not always be the same. There are times when information is not fully available or trading is swayed by emotional reactions and the market value invesments diverges from the financial value.We will not attempt to analyze these periods of divergence. Our basic premise in this topic is that economic forces will ultimately bring that market value into line with the underlying financial value. Our focus will be on the elements and techniques of determining the financial value of an invesment.